IDENTIFIKASI POLA AGROFORESTRI DI DESA TOGID, KECAMATAN TUTUYAN, KABUPATEN BOLAANG MONGONDOW TIMUR - Yuliyana Christina Laratmase; Semuel P. Ratag; Euis F. S. Pangemanan (COCOS, 2022)
Abstract Agroforestry is a system of land use in which forestry crops (woody perennial) is combined with agriculture crops and livestock or fisheries in one unit of land. There has been no data and informations on agroforestry patterns in Togid Village, Tutuyan District, East Bolaang Mongondow Regency until now . This study aims to describe agroforestry patterns in Togid Village, Tutuyan District, Bolaang Mongondow Timur Regency in February 2021. The methods used in this study are field surveys, interviews and data retrieval. Respondents were obtained by purposive sampling with the criteria that farmers practice agroforestry systems in cultivating their respective gardens. The data obtained were then analyzed descriptively and presented in tabular form.. The results showed that there are two agroforestry patterns applied by farmers, namely the agrisilvicultural pattern and the agrosilvopasture-fishery pattern. There are nine combinations of 14 respondents' garden lands that are cultivated with plants - animals - fish.One of the 14 respondent's gardens is cultivated with an agrosilvopasture-fishery pattern, carried out by one respondent, while the other 13 gardens are cultivated with an agrosilvicultural pattern. In combination with woody plants, from 14 observed gardens, it was found that there were food crops in eight gardens, spice plants in nine gardens, ornamental plants in three gardens, fodder sources in caged livestock in four gardens, and fish in one. garden land The existence of a garden with an agroforestry pattern can make a very significant contribution to the community in Togid Village both in terms of economy and ecology Keywords: Agroforestry Pattern, Togid village